Pembelajaran Berbasis Project Based Learning Untuk Meningkatkan Penguatan Profil Pelajar Pancasila Ketrampilan Berpikir Kritis dan Kreatif Siswa Kelas II Sekolah Dasar - Widyawati, Lely (Universitas Sebelas Maret, 2022)
This research aims to provide a description of the results of good practice in implementing project based learning to increase the strengthening of the Pancasila student profile, critical and creative thinking skills in grade 2 elementary school students. The research method used is a descriptive qualitative research method with data collection techniques through observation and survey methods during the learning process. The research results from this good practice have a positive impact on student learning outcomes, especially in each project based learning learning syntax and provide an increase in students' critical and creative thinking skills. From the results of data analysis, it was obtained that the percentage increase in students' critical thinking skills increased from 60% to 80% and students' creative thinking skills increased from 65% to 85%. So it can be concluded that project based learning is a reference learning model that can be used by teachers to strengthen the profile of Pancasila students, especially in the elements of critical and creative thinking skills for grade 2 elementary school students.